Atlas and Anatomy of PET/MRI, PET/CT and SPECT/CT - Kim, E. Edmund; Im, Hyung-jun; Lee, Dong Soo; Kang, Keon Wook (Springer International Publishing : Imprint: Springer, 2016)
This atlas showcases cross-sectional anatomy for the proper interpretation of images generated from PET/MRI, PET/CT, and SPECT/CT applications. Hybrid imaging is at the forefront of nuclear and molecular imaging and enhances data acquisition for the purposes of diagnosis and treatment. Simultaneous evaluation of anatomic and metabolic information about normal and abnormal processes addresses complex clinical questions and raises the level of confidence of the scan interpretation. Extensively illustrated with high-resolution PET/MRI, PET/CT and SPECT/CT images, this atlas provides precise morphologic information for the whole body as well as for specific regions such as the head and neck, abdomen, and musculoskeletal system. Atlas and Anatomy of PET/MRI, PET/CT, AND SPECT/CT is a unique resource for physicians and residents in nuclear medicine, radiology, oncology, neurology, and cardiology. .